Decorative laminate for three-dimensional molding and method for manufacturing the same
Patent Information
- Application Number
- JP2023138283
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-12
AI Technical Summary
【0012】 本開示によれば、三次元成形加工後の耐腐食性、耐衝撃性、接着性、及び耐口開き性に優れる、三次元成形加工用装飾積層体及びその製造方法することができる。
Smart Images

Figure 2025032802000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a decorative laminate that is subjected to three-dimensional forming processing and a method for producing the same. [Background technology]
[0002] In recent years, for example, decorative laminates containing a polyurethane resin layer have been developed and are used in a wide range of fields such as exterior parts.
[0003] Patent Document 1 (JP-A-05-155976) describes the use of a laminate including a specific polyurethane resin layer and a heat-sensitive adhesive layer as an interior / exterior film.
[0004] Patent Document 2 (JP 2007-297569 A) describes a decorative layer-forming film having a topcoat layer made of a polyurethane resin and a carrier film provided on the surface side of the topcoat layer, in which the polyurethane resin is made of a polyurethane resin composition that contains (1) a polyisocyanate containing an isocyanurate or adduct of isophorone diisocyanate or both of them in an amount of 0.5 or more equivalents relative to the total polyisocyanate, and (2) a polyol consisting of caprolactone diol, polycarbonate diol, or a mixture thereof and containing a polyester polyol having an average molecular weight of 1000 or less in an amount of 0.4 or more equivalents relative to the total polyol, and in which the equivalent ratio of polyisocyanate to polyol is 0.7 to 2.0. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 05-155976 [Patent Document 2] JP 2007-297569 A Summary of the Invention [Problem to be solved by the invention]
[0006] Metal substrates may corrode when exposed to wind, rain, chemicals, etc., and in order to prevent such corrosion, a resin layer may be applied to the metal substrate. Among resin layers, polyurethane resin layers have excellent impact resistance, and therefore can suitably prevent defects such as cracking of the resin layer after impact. However, polyurethane resin layers have poor adhesion to metal substrates, so when applying a polyurethane resin layer to a metal substrate, it has been necessary to use an adhesive layer (e.g., a heat-sensitive adhesive layer). The adhesive layer is generally thicker and more flexible than a primer layer, so that, for example, when a laminate including a metal substrate, an adhesive layer, and a polyurethane resin layer is subjected to three-dimensional molding, the polyurethane resin layer may break, or even if it does not break, if a cut is made in the polyurethane resin layer, a phenomenon in which the cut opens over time may occur. For example, when the polyurethane resin layer is stretched during molding such as deep drawing, and a cut is made in the polyurethane resin layer in that state and heat is applied, the polyurethane resin layer tries to return to its original state. Since a flexible adhesive layer cannot restrain the return, the phenomenon in which the cut opens is likely to occur.
[0007] The present disclosure provides a decorative laminate for three-dimensional forming processing, which has excellent corrosion resistance, impact resistance, adhesion, and opening resistance after three-dimensional forming processing, and a method for producing the same. [Means for solving the problem]
[0008] According to one embodiment of the present disclosure, there is provided a method for producing a decorative laminate for three-dimensional molding processing, comprising: preparing a metal layer; applying a primer layer to the metal layer, the primer layer comprising at least one selected from the group consisting of an organosilicon compound and a (meth)acrylic resin; directly applying a two-component curing polyurethane precursor layer to the primer layer, the two-component curing polyurethane precursor layer comprising a polyol and an isocyanate; and reacting the two-component curing polyurethane precursor layer to form a polyurethane layer.
[0009] According to another embodiment of the present disclosure, there is provided a decorative laminate for three-dimensional forming processing, which comprises, in order, a metal layer, a primer layer, and a polyurethane layer, wherein the primer layer comprises at least one selected from the group consisting of an organosilicon compound and a (meth)acrylic resin; the polyurethane layer comprises a cured reaction product of a two-component curing polyurethane resin composition comprising a polyol and an isocyanate; the polyurethane layer is directly applied to the primer layer; and when the polyurethane layer of the laminate is subjected to the water resistance test described below, the polyurethane layer achieves a remaining square count of 90 / 100 or more, and when the polyurethane layer of the laminate is subjected to the heat resistance test described below, the polyurethane layer exhibits a maximum opening width or peel width of 0.5 mm or less. <Water resistance test> The decorative laminate for three-dimensional molding is immersed in 40°C water for 240 hours, the laminate is removed, the water is wiped off, and left to stand for 1 hour. After that, a total of 100 1mm square 10 x 10 squares are cut into the polyurethane layer of the laminate with a cutter, and Scotch tape (registered trademark) is applied to the 100 squares. The Scotch tape (registered trademark) is then immediately removed and the number of squares remaining where the polyurethane layer has not peeled off is counted. <Heat resistance test> Using a DuPont drop impact tester No. 517, a decorative laminate for three-dimensional molding is placed on a receiving base with a recess, covering the recess and with the metal layer facing up. A hemispherical die with a 1 / 2 inch diameter tip is placed in contact with the top surface of the metal layer, and a 1 kg weight is dropped from a height of 50 cm onto the die to deform the laminate into a convex shape. A cross-shaped cut is made in the polyurethane layer of the laminate that has been deformed into a convex shape with a cutter blade. The laminate is then subjected to the following heat cycle, after which the opening width and peel width of the polyurethane layer at the cut are confirmed: (Thermal Cycle) (1) Heat the container from 23°C to 80°C over one hour. (2) Maintain at 80°C for 18 hours. (3) The temperature is lowered to -30°C over one hour. (4) Keep at -30°C for 4 hours. (5) Heat to 80°C over 1 hour. (6) Keep at 80°C for 18 hours. Repeat steps (3) to (6) above nine times. (7) The temperature is reduced to -30°C over one hour. (8) Keep at -30°C for 4 hours. (9) The temperature is raised from -30°C to 23°C over one hour.
[0010] According to another embodiment of the present disclosure, a decorative article is provided that includes the decorative laminate described above, having a three-dimensional shape.
[0011] According to another embodiment of the present disclosure, there is provided a method for producing a decorative article, comprising pressing or roll-forming the decorative laminate described above. Effect of the Invention
[0012] According to the present disclosure, it is possible to provide a decorative laminate for three-dimensional molding that has excellent corrosion resistance, impact resistance, adhesion, and opening resistance after three-dimensional molding, and a method for manufacturing the same.
[0013] The above description should not be considered as a disclosure of all embodiments of the present invention and all advantages associated with the present invention. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view of a conventional decorative laminate. [Diagram 2] FIG. 2 is a schematic diagram of a cross section of a decorative laminate for three-dimensional molding according to one embodiment of the present disclosure. [Diagram 3]FIG. 3(a) is an external photograph of the decorative articles (automotive molding parts) of Examples 1 to 4 of the present application obtained by three-dimensionally molding a decorative laminate for three-dimensional molding processing of one embodiment of the present disclosure, (b) is an external photograph of the decorative article (automotive molding part) of Example 7 of the present application obtained by three-dimensionally molding a decorative laminate for three-dimensional molding processing of another embodiment of the present disclosure, and (c) is an external photograph of the decorative article (automotive molding part) of Example 8 of the present application obtained by three-dimensionally molding a decorative laminate for three-dimensional molding processing of another embodiment of the present disclosure. [Figure 4] FIG. 4(a) is a perspective view showing a test using a DuPont No. 517 drop impact tester, and FIG. 4(b) is a cross-sectional view showing the state before and after the test. [Diagram 5] (a) in Figure 5 is a schematic diagram of a convex portion formed on a decorative laminate for three-dimensional molding processing, and (b) is a schematic diagram of a convex portion formed on the decorative laminate for three-dimensional molding processing after a cross-shaped cut has been made in the polyurethane layer of the convex portion with a cutter. [Figure 6] FIG. 6 is a photograph of a decorative laminate for three-dimensional forming according to one embodiment of the present disclosure pressed into a hat-like shape. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, for the purpose of illustrating representative embodiments of the present invention, the present invention will be described in more detail with reference to the drawings as necessary, but the present invention is not limited to these embodiments. Regarding the reference numbers of the drawings, elements with similar numbers in different drawings indicate similar or corresponding elements.
[0016] In this disclosure, "three-dimensional molding" refers to molding into a three-dimensional shape, and "three-dimensional shape" refers to a three-dimensional shape in which the Z axis is added to a two-dimensional shape (a planar shape with only the X axis and Y axis). Here, the "three-dimensional shape" in this disclosure can also include, for example, a curved shape.
[0017] In the present disclosure, for example, "on" in "the primer layer is disposed on the metal layer" intends that the primer layer is disposed directly on the upper side of the metal layer, or that the primer layer is disposed indirectly on the upper side of the metal layer via another layer.
[0018] In the present disclosure, for example, "under" in "the metal layer is disposed under the primer layer" intends that the metal layer is disposed directly under the primer layer, or that the metal layer is disposed indirectly under the primer layer via another layer.
[0019] In the present disclosure, "transparent" refers to an average transmittance of about 80% or more, preferably about 85% or more, or about 90% or more, in the visible light region (wavelength 400 nm to 700 nm) measured in accordance with JIS K 7375. There is no particular limit to the upper limit of the average transmittance, but it can be, for example, less than about 100%, about 99% or less, or about 98% or less.
[0020] In the present disclosure, the term "semi-transparent" refers to an average transmittance in the visible light region (wavelength 400 nm to 700 nm) measured in accordance with JIS K 7375 of less than about 80%, desirably about 75% or less, and is intended to not completely conceal the base.
[0021] In the present disclosure, "(meth)acrylic" means acrylic or methacrylic.
[0022] In the present disclosure, the term "sheet" also encompasses a member called a "film."
[0023] Hereinafter, with reference to the drawings as necessary, the decorative laminate for three-dimensional molding processing of the present disclosure (sometimes simply referred to as "laminate" or "decorative laminate") and its manufacturing method will be described.
[0024] A conventional decorative laminate 100 shown in Fig. 1 includes a metal layer 101, a primer layer 103, an adhesive layer 105, and a polyurethane layer 107. On the other hand, the decorative laminate of the present invention, as shown in Fig. 2, can bond a metal layer 201 and a polyurethane layer 207 together by a primer layer 203 without using an adhesive layer.
[0025] In the conventional decorative laminate, the cured polyurethane layer is applied to the metal layer in the form of, for example, a film, so that the primer layer alone does not provide sufficient adhesive strength, and an adhesive layer made of a heat-sensitive polyurethane adhesive or the like is required separately. On the other hand, the manufacturing method of the decorative laminate of the present disclosure includes preparing a metal layer; applying a primer layer containing at least one selected from the group consisting of an organosilicon compound and a (meth)acrylic resin to the metal layer; directly applying a two-component curing polyurethane precursor layer containing a polyol and an isocyanate to the primer layer; and reacting the two-component curing polyurethane precursor layer to form a polyurethane layer. In other words, the manufacturing method of the decorative laminate of the present disclosure is different from the conventional manufacturing method in that, instead of applying a cured polyurethane layer to the primer layer, an uncured polyurethane layer (polyurethane precursor layer) before curing is directly applied to the primer layer, and then the polyurethane layer (polyurethane precursor layer) is subjected to a curing reaction. By going through such a process, the adhesive strength between the polyurethane layer and the primer layer is improved, so that the polyurethane layer and the metal layer can be suitably bonded without using an adhesive layer made of a heat-sensitive polyurethane adhesive or the like that has been used in the past.
[0026] The decorative laminate of the present disclosure does not use a generally flexible adhesive layer such as a heat-sensitive polyurethane adhesive layer, and therefore, compared to conventional decorative laminates, it is possible to reduce or prevent the tearing of the polyurethane layer after three-dimensional molding or the opening phenomenon caused by a cut in the polyurethane layer over time. Therefore, the decorative laminate of the present disclosure can be suitably used for three-dimensional molding.
[0027] Adhesive layers such as heat-sensitive polyurethane adhesive layers are generally flexible layers, so that when a polyurethane layer is applied on such an adhesive layer, the decorative laminate becomes soft. As a result, for example, when the surface of the decorative laminate is pressed, defects such as indentations or scratches may occur on the surface of the decorative laminate. The decorative laminate of the present disclosure does not use a generally flexible adhesive layer such as a heat-sensitive polyurethane adhesive layer, so that the hardness of the entire decorative laminate can be improved and defects such as indentations or scratches can be reduced or suppressed. In addition, according to the manufacturing method of the present disclosure, since it is not necessary to use an adhesive layer such as a heat-sensitive polyurethane adhesive layer, it can also contribute to reducing the manufacturing cost of the decorative laminate.
[0028] The metal layer that can be used in the method for producing the decorative laminate of the present disclosure is not particularly limited, and may be, for example, a layer containing a metal selected from aluminum, nickel, gold, silver, copper, platinum, chromium, iron, steel, stainless steel, tin, indium, titanium, lead, zinc, germanium, etc., or an alloy or compound thereof. The metal layer may be a single layer or a laminated layer. Among them, stainless steel is preferred from the viewpoint of three-dimensional moldability and corrosion resistance.
[0029] The thickness of the metal layer is not particularly limited as long as it is a thickness that allows three-dimensional molding. The thickness of the metal layer can be, for example, about 100 micrometers or more, about 150 micrometers or more, about 200 micrometers or more, about 250 micrometers or more, about 300 micrometers or more, or about 350 micrometers or more, and can be about 3 mm or less, about 2 mm or less, about 1 mm or less, about 800 micrometers or less, or about 500 micrometers or less. The thickness of each layer in the decorative laminate of the present disclosure can be defined as, for example, the average value of the thickness of at least five arbitrary locations in the metal layer measured with a thickness gauge (PC-465N manufactured by TECLOCK). When the layers constituting the laminate are thin and difficult to measure with a thickness gauge, the thickness direction cross section of the laminate structure can be measured using a scanning electron microscope, and the thickness can also be defined as the average value of the thickness of at least five arbitrary locations in the target layer of the laminate structure, for example, the primer layer.
[0030] Generally, the surface of the metal layer may be contaminated with oil or the like. Therefore, the surface of the metal layer may be subjected to a surface treatment such as degreasing or cleaning. Examples of such a surface treatment method include a method of wiping the surface of the metal layer with an organic solvent such as alcohol, an alkaline aqueous solution such as sodium hydroxide, or other cleaning liquid (these may be collectively referred to simply as "cleaning agent"). A method of immersing the metal layer in a cleaning agent, and a method of spraying the cleaning agent at high pressure. The surface of the metal layer may be subjected to a surface treatment such as a corona treatment or a plasma treatment. If a primer layer is applied to the metal layer that has been subjected to such a surface treatment, the adhesion between the polyurethane layer and the metal layer can be further improved.
[0031] The primer layer that can be used in the method for producing the decorative laminate of the present disclosure contains at least one selected from the group consisting of an organosilicon compound and a (meth)acrylic resin. The amounts of the organosilicon compound and the (meth)acrylic resin can be appropriately mixed so as to obtain a desired adhesive strength. For example, each of these components can be contained in a range of about 50% by mass or more, about 60% by mass or more, about 70% by mass or more, or about 80% by mass or more, about 100% by mass or less, or less than about 100% by mass, based on the total amount of the primer layer. In the present disclosure, a primer containing an organosilicon compound may be referred to as a silane-based primer, and a primer containing a (meth)acrylic resin may be referred to as an acrylic-based primer.
[0032] The primer layer may be applied directly to the metal layer. From the viewpoint of adhesion between the polyurethane layer and the metal layer, it is preferable that the primer layer is applied directly to the metal layer. When an arbitrary layer such as a decorative layer is interposed between the metal layer and the primer layer, it is preferable to partially apply the arbitrary layer to the metal layer so that a portion where the metal layer and the primer layer are in direct contact with each other is generated. The primer layer can be applied by a known coating method or the like. When applying the primer layer to the metal layer, additional steps such as a drying step (e.g., drying at room temperature) and a heating step (e.g., heating by an oven or infrared rays) may be appropriately adopted as necessary.
[0033] The primer layer can improve the adhesion of an uncured polyurethane layer (polyurethane precursor layer) applied on the primer layer after a curing reaction.
[0034] Among the materials constituting the primer layer, organosilicon compounds are preferred. Adhesive layers such as heat-sensitive adhesive layers used in conventional decorative laminates, and primer layers containing (meth)acrylic resins, are poor in weather resistance, so the polyurethane layer applied on these layers may need to be colored black to block light. Since organosilicon compounds have excellent weather resistance, when a primer layer containing an organosilicon compound is used, the polyurethane layer does not need to be colored, and a transparent polyurethane layer can be used. As a result, the decorative performance of the metal layer itself, such as metallic luster, can be visually recognized.
[0035] As the organosilicon compound, a compound having an alkoxysilyl group having a silicon atom and 1 to 3 alkoxy groups covalently bonded to the silicon atom can be used. From the viewpoint of adhesion between the polyurethane layer and the metal layer, a compound having a structure in which two or more alkoxy groups are covalently bonded to a silicon atom is preferred, and a compound having a structure in which three alkoxy groups are covalently bonded to a silicon atom is more preferred. Examples of the alkoxy group include a methoxy group, an ethoxy group, an isopropoxy group, an n-butoxy group, and a t-butoxy group. Among these, from the viewpoint of adhesion between the polyurethane layer and the metal layer, a methoxy group and an ethoxy group are preferred. The organosilicon compound may have an epoxy group, a methacryl group, an acrylic group, an amino group, or a styryl group. Among these, from the viewpoint of adhesion between the polyurethane layer and the metal layer, an amino group is preferred. The organosilicon compound can be used alone or in combination of two or more kinds. As the organosilicon compound, an agent generally called a silane coupling agent can be used.
[0036] Specific examples of the organosilicon compound include γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-N'-β-(aminoethyl)-γ-aminopropyltriethoxysilane, γ-anilinopropyltriethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltriethoxysilane, vinyltriethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, and γ-isocyanatepropyltriethoxysilane.
[0037] The (meth)acrylic resin is not particularly limited, and for example, a commercially available (meth)acrylic resin used as a primer can be used. For example, the primer containing the (meth)acrylic resin can be KBS17A / B manufactured by Konishi Co., Ltd. (Osaka City, Osaka, Japan), which is commercially available as an acrylic primer, or Hamatite (trademark) A-1100F manufactured by Sika Japan Co., Ltd. (Minato Ward, Tokyo, Japan), which is commercially available as an acrylic primer.
[0038] The thickness of the primer layer can be about 10 micrometers or less, less than about 10 micrometers, about 8 micrometers or less, or about 6 micrometers or less. From the viewpoints of adhesion between the metal layer and the polyurethane layer, resistance to opening, and hardness of the entire decorative laminate, the thickness of the primer layer is preferably about 5 micrometers or less, about 4 micrometers or less, or about 3 micrometers or less. There is no particular limit to the lower limit of the thickness of the primer layer, and it can be, for example, about 0.05 micrometers or more, about 0.5 micrometers or more, or about 1 micrometer or more.
[0039] In some embodiments, the primer layer may contain, as optional components, for example, fillers, reinforcing materials, antioxidants, flame retardants, UV absorbers, light stabilizers, heat stabilizers, flame retardants, dispersants, plasticizers, flow improvers, tackifiers, leveling agents, catalysts, pigments, dyes, thickeners, organosilicon compounds, and binder resins other than (meth)acrylic resins, depending on the intended use, etc. The optional components may be used alone or in combination of two or more.
[0040] The method for producing a decorative laminate of the present disclosure includes directly applying a two-component curing polyurethane precursor layer (sometimes simply referred to as a "precursor layer") containing a polyol and an isocyanate to the above-mentioned primer layer, and reacting the two-component curing polyurethane precursor layer to form a polyurethane layer. Here, "directly applying the two-component curing polyurethane precursor layer to the primer layer" may include directly applying the two-component curing polyurethane precursor layer to a part of the primer layer in addition to directly applying the two-component curing polyurethane precursor layer to the entire surface of the primer layer. The two-component curing polyurethane precursor layer can be applied by a known coating method, lamination method, or the like. When applying the two-component curing polyurethane precursor layer to the primer layer, or when reacting the two-component curing polyurethane precursor layer to form a polyurethane layer, additional steps such as a drying step (e.g., drying at room temperature) and a heating step (e.g., heating by an oven or infrared rays) may be appropriately adopted as necessary.
[0041] The two-component curing polyurethane precursor layer may be a single layer structure or a laminated structure (e.g., a colored layer and a clear surface layer). In the case of a laminated structure, at least the layer directly applied to the primer layer is a two-component curing polyurethane precursor layer. In the case of a laminated structure, from the viewpoint of adhesion between the polyurethane layer and the metal layer, it is preferable that the layers other than the layer directly applied to the primer layer are also two-component curing polyurethane precursor layers, and it is preferable to carry out the curing reaction after laminating all the precursor layers on the primer layer.
[0042] In the present disclosure, the term "two-component curing polyurethane precursor layer" refers to a polyurethane layer that is not completely cured and is in an uncured state. Whether the polyurethane layer is in an uncured state or in a completely cured state can be evaluated, for example, using a Fourier transform infrared spectrometer (FT-IR Nicolet iS5, manufactured by Yamato Scientific Co., Ltd. (Chuo-ku, Tokyo, Japan)). Specifically, the polyurethane layer is measured with such a device, and the 2270 cm -1 If the N=C=O inverse symmetric stretching peak present in the vicinity can be observed, it can be evaluated that the curing is not complete, and if the wavelength range is almost flat and no peak can be observed, it can be evaluated that the curing is complete. Alternatively, from the evaluation results of the water resistance test and heat resistance test described later performed on the obtained decorative laminate, it can be indirectly evaluated whether or not the polyurethane layer when directly applied to the primer layer by the manufacturing method of the decorative laminate of the present disclosure was an uncured polyurethane precursor layer. That is, if the evaluation results of the water resistance test and heat resistance test are at the pass level, it can be considered that the uncured polyurethane precursor layer was directly applied to the primer layer, and if they are at the fail level, it can be considered that the polyurethane layer in a completely cured state was directly applied to the primer layer.
[0043] The two-component curing polyurethane precursor layer may be, for example, an uncured polyurethane sheet or an uncured polyurethane coating layer. The adjustment of the uncured and cured states in the two-component curing polyurethane can be controlled, for example, by adjusting the temperature conditions, the curing reaction time, or the amount of the catalyst. In some embodiments, the following method can be used to prepare an uncured polyurethane layer (a polyurethane layer in a state where the polyurethane layer is dry but has isocyanate groups remaining). After applying the two-component curing polyurethane resin composition to a substrate or the like, the polyurethane layer is dried so that the solvent content is substantially eliminated without foaming. At this time, with respect to the polyurethane layer of the clear surface layer, it is preferable that the polyurethane layer has a softness such that the polyurethane layer can be laminated to a PET film without air being trapped in the polyurethane layer when the isocyanate groups remain, that the polyurethane layer is not in a state where the polyurethane layer is washed away by the pressure during lamination, and that when the polyurethane layer is touched with a fingertip and then immediately removed from the fingertip, the polyurethane layer has a fingerprint but does not adhere to the finger. With respect to the polyurethane layer of the colored layer, it is preferable that the surface of the polyurethane layer is not sticky when the isocyanate groups remain. Here, from the viewpoint of evaporating the solvent without foaming, the temperature during drying can be, for example, about 60°C or more, about 70°C or more, or about 80°C or more, about 150°C or less, about 130°C or less, or about 110°C or less. The curing reaction time can vary depending on the applied temperature or the amount of catalyst to be described later, and can be, for example, about 1 minute or more, about 2 minutes or more, or about 3 minutes or more, about 1 hour or less, about 30 minutes or less, or about 10 minutes or less. The amount of catalyst to be added can be unnecessary in the case of acrylic polyols, etc., which react quickly. In the case of polycaprolactone polyols, etc., which react slowly compared to acrylic polyols, it is preferable to add a catalyst, and the amount of catalyst to be added can be about 0.01% by mass or more, about 0.02% by mass or more, or about 0.04% by mass or more, about 0.4% by mass or less, about 0.2% by mass or less, or about 0.1% by mass or less, based on the solid content of the polyurethane layer (especially the clear polyurethane layer).The uncured polyurethane precursor layer can maintain the uncured state for about one week in an atmosphere at room temperature (about 20° C.±about 15° C.) or lower, and can maintain the uncured state for about several weeks at around 0° C. Therefore, even an uncured polyurethane sheet that has been stored for several days can be suitably used as the two-component curing polyurethane precursor layer of the present disclosure.
[0044] The polyurethane precursor layer directly applied to the primer layer can be subjected to the curing reaction of polyurethane by controlling the temperature conditions and the curing reaction time as described above, or by controlling the storage temperature and storage time, to form a polyurethane layer. The storage temperature and storage time can be, for example, about 10 days or more, about 2 weeks or more, about 3 weeks or more, or about 30 days or more at room temperature.
[0045] The polyurethane layer of the present disclosure is prepared using a two-component curing polyurethane resin composition containing a polyol and an isocyanate. Here, the term "isocyanate" in the present disclosure includes isocyanates called polyisocyanates in addition to isocyanates as monomers.
[0046] Examples of polyols include polyether polyols; polymer polyols having a carbon-carbon bond in the main chain such as (meth)acrylic polyols, polybutadiene diols, and hydrogenated polybutadiene polyols; and polyester polyols such as polycaprolactone polyols and polycarbonate polyols. Among them, polyester polyols are preferred because they can improve the breaking elongation, especially the breaking elongation at high temperatures, and polycarbonate polyols and polycaprolactone polyols are more preferred, and polycaprolactone polyols are particularly preferred. Examples of polycarbonate polyols include polycarbonate diols, and examples of polycaprolactone polyols include polycaprolactone diols and polycaprolactone triols. From the viewpoint of adhesion between the polyurethane layer and the metal layer, it is preferable that the polycarbonate polyol, the polycaprolactone polyol, or both of them are contained in an amount of about 40% or more, about 50% or more, about 60% or more, about 70% or more, about 80% or more, or about 90% or more based on the total polyols in terms of equivalent weight. The polyols can be used alone or in combination of two or more kinds. When a pigment is dispersed to color the film, (meth)acrylic polyols are preferable.
[0047] In some embodiments, the polyol contains about 0.4 equivalents or more of polyester polyol having an average molecular weight of about 1,000 or less relative to the total polyol. When about 0.4 equivalents or more of polyester polyol having an average molecular weight of about 1,000 or less is contained, the breaking elongation at high temperature can be improved. From the viewpoint of breaking elongation at high temperature, polycarbonate polyol and polycaprolactone polyol are preferred. Here, the average molecular weight of the polyol refers to the number average molecular weight based on polystyrene standard measured by gel permeation chromatography (GPC).
[0048] Specific examples of polyester polyols include polycaprolactone diols such as "TONE (trademark) 0201" (manufactured by Dow Chemical Company, Midland, Michigan, USA; average molecular weight 530), "PLAXEL (trademark) 205" (manufactured by Daicel Corporation, Minato-ku, Tokyo, Japan; average molecular weight 530), "PLAXEL (trademark) 205H" (manufactured by Daicel Corporation; average molecular weight 530), "PLAXEL (trademark) 208" (manufactured by Daicel Corporation; average molecular weight 850), and "PLAXEL (trademark) 210" (manufactured by Daicel Corporation; average molecular weight 1000); "TONE (trademark) 0301" (manufactured by Dow Chemical Company; average molecular weight 300), "TONE (trademark) 1303" (manufactured by Daicel Corporation; average molecular weight 1000); Polycaprolactone triols such as "TONE (trademark) 0305" (manufactured by Dow Chemical Company; average molecular weight 425), "TONE (trademark) 0305" (manufactured by Dow Chemical Company; average molecular weight 540), "Placcel (trademark) 305" (manufactured by Daicel Corporation; average molecular weight 550), and "Placcel (trademark) 308" (manufactured by Daicel Corporation; average molecular weight 850); polycarbonate diols such as "Nippolan (trademark) 981" and "Nippolan (trademark) 983" (manufactured by Tosoh Corporation, Minato-ku, Tokyo, Japan; average molecular weight 1000), "T4671", "T4691" and "T5651" (all manufactured by Asahi Kasei Corporation, Chiyoda-ku, Tokyo, Japan; average molecular weight 1000) can be used.
[0049] In the polyester polyol, when polycaprolactone diol and polycarbonate diol are used in combination, these diols can be used in various amount ratios. For example, the equivalent ratio of polycaprolactone diol and polycarbonate diol can be set from about 1: about 9, about 2: about 8, about 3: about 7, about 4: about 6, about 5: about 5, about 6: about 4, about 7: about 3, about 8: about 2, about 9: about 1. When these diols are mixed in such a ratio, the average molecular weight in that state can be about 1,000 or less, preferably about 850 or less, more preferably about 750 or less, and most preferably about 500 to about 600.
[0050] When polycaprolactone diol is used alone, its average molecular weight can be about 700 or less, and preferably in the range of about 500 to about 600.
[0051] The isocyanate may be at least one selected from the group consisting of isocyanates having a cyclohexane structure, isocyanates having no carbon-carbon double bond, and isocyanates having a branched structure. Examples of the isocyanates having a branched structure include trimers, biurets, and adducts of isocyanates.
[0052] In some embodiments, the isocyanate may contain, for example, a trimer, biuret, adduct, or a mixture of two or three of isophorone diisocyanate (IPDI) or 1,3-bis(isocyanatomethyl)cyclohexane (H6XDI) in an amount of about 0.5 equivalents or more relative to the total isocyanate. Since such an isocyanate can improve the breaking elongation, particularly the breaking elongation at high temperatures, a trimer or adduct of isophorone diisocyanate or 1,3-bis(isocyanatomethyl)cyclohexane is more preferred. Because this can improve the breaking elongation, particularly the breaking elongation at high temperatures, it is preferable that the trimer, adduct, or mixture of these of isophorone diisocyanate or 1,3-bis(isocyanatomethyl)cyclohexane is contained in an amount, in equivalent terms, of about 50% or more, about 60% or more, about 70% or more, about 80% or more, or about 90% or more relative to the total isocyanate.
[0053] Trimers of isophorone diisocyanate can be obtained, for example, from Sumika Covestro Urethane Co., Ltd. (Amagasaki, Hyogo Prefecture, Japan) under the trade name "Desmodur (trademark) Z4370" or from Evonik Japan Co., Ltd. (Shinjuku-ku, Tokyo, Japan) under the trade name "VESTNAT (trademark) T1890". Adducts of isophorone diisocyanate are adducts of isophorone diisocyanate with trimethylolpropane, trimethylolethane, pentaerythritol, etc., and adducts with trimethylolpropane can be obtained, for example, from Takeda Pharmaceutical Co., Ltd. (Chuo-ku, Tokyo, Japan) under the trade name "Takenate (trademark) D-140N". Trimers of 1,3-bis(isocyanatomethyl)cyclohexane can be obtained, for example, from Mitsui Chemicals, Inc. (Chuo-ku, Tokyo, Japan) under the trade name "D-127N". The adduct of 1,3-bis(isocyanatomethyl)cyclohexane is available, for example, from Mitsui Chemicals Inc. (Chuo-ku, Tokyo, Japan) under the trade name "D-120N."
[0054] The equivalent ratio of isocyanate to polyol in the polyurethane resin composition may be appropriately adjusted so as to obtain the desired performance (e.g., protective performance) of the polyurethane layer. For example, the equivalent ratio of isocyanate to polyol (isocyanate / polyol) may be in the range of about 0.7 or more, about 0.8 or more, about 0.9 or more, or about 1.0 or more, about 2.0 or less, about 1.8 or less, about 1.6 or less, or about 1.5 or less. When the equivalent ratio of isocyanate to polyol is in this range, the adhesion between the polyurethane layer and the metal layer is excellent, and the breaking elongation, especially the breaking elongation at high temperatures, weather resistance, chemical resistance, and scratch resistance can also be improved.
[0055] A polyurethane resin composition containing an isocyanate and a polyol can be prepared into a polyurethane resin by appropriately using a known method. For example, polymerization can be carried out in a state where a catalyst is blended in the polyurethane resin composition. As such a catalyst, a commonly used catalyst can be used, for example, a dibutyltin dilaurate (DBTDL) catalyst, zinc naphthenate, zinc octenate, triethylenediamine, etc. can be used. The amount of the catalyst can be about 0.005% by mass to about 0.5% by mass with respect to 100% by mass of the resin composition.
[0056] The polyurethane layer obtained by reacting the two-component curing polyurethane precursor layer may have a single layer structure or a laminate structure. In the case of a laminate structure, for example, the polyurethane layer may be a laminate of films formed from the polyurethane resin composition, or may be a multi-layer coating of the resin composition. The polyurethane layer may be colored or colorless. The polyurethane layer may be opaque, semi-transparent, or transparent. The polyurethane layer may have an uneven shape such as an embossed pattern on the entire surface or a part of the surface.
[0057] The polyurethane layer can be formed, for example, by applying the polyurethane resin composition to the primer layer using a known coating method such as knife coating or bar coating. Alternatively, the resin composition can be coated on a release liner to form a polyurethane precursor film, which can be laminated on the primer layer and then cured to form the polyurethane layer. Alternatively, an uncured polyurethane precursor film previously formed into a film shape by extrusion, stretching, or the like can be laminated on the primer layer and then cured to form the polyurethane layer.
[0058] The thickness of the polyurethane layer may be appropriately adjusted depending on the desired performance (e.g., protective performance), etc. The thickness may be, for example, about 1 micrometer or more, about 3 micrometers or more, about 5 micrometers or more, about 7 micrometers or more, or about 10 micrometers or more, and about 50 micrometers or less, about 40 micrometers or less, about 30 micrometers or less, or about 20 micrometers or less.
[0059] The polyurethane layer of the present disclosure may contain, as optional components, within the scope of not adversely affecting the effects of the present disclosure, fillers, matting agents, antioxidants, UV absorbers, light stabilizers, heat stabilizers, flame retardants, hard coat materials, gloss-imparting agents, dispersants, plasticizers, flow improvers, surfactants, leveling agents, silane coupling agents, catalysts, pigments, dyes, etc. The optional components may be used alone or in combination of two or more.
[0060] According to the manufacturing method of the decorative laminate of the present disclosure, the two-component curing polyurethane precursor layer is directly applied to the primer layer, and then the precursor layer is reacted to form a polyurethane layer, so that the adhesiveness and opening resistance are excellent. Therefore, when the decorative laminate of the present disclosure is subjected to the water resistance test shown below, the polyurethane layer can achieve a remaining number of squares of 90 / 100 or more, 95 / 100 or more, or 97 / 100 or more, 100 / 100 or less, or 99 / 100 or less, and when the decorative laminate of the present disclosure is subjected to the heat resistance test shown below, the polyurethane layer can exhibit an opening width and / or peel width of about 0.5 mm or less, about 0.4 mm or less, about 0.3 mm or less, about 0.2 mm or less, or about 0.1 mm or less, about 0 mm or more, or more than about 0 mm. Here, the configuration of each layer of the decorative laminate of the present disclosure (e.g., the material and thickness of each layer, etc.) can be similarly adopted to the configuration described above in the manufacturing method of the decorative laminate of the present disclosure.
[0061] <Water resistance test> The decorative laminate is immersed in 40°C water for 240 hours, the laminate is removed, the water is wiped off, and the laminate is left to stand for 1 hour. After that, a total of 100 1mm square squares (10 x 10) are created in the polyurethane layer of the laminate with a cutter, and Cellotape (registered trademark) CT-24 (manufactured by Nichiban Co., Ltd., Bunkyo-ku, Tokyo, Japan) is applied to the 100 squares. The Cellotape (registered trademark) is then immediately removed and the number of squares remaining where the polyurethane layer has not peeled off is counted.
[0062] <Heat resistance test> Using a No. 517 DuPont drop impact tester (manufactured by Yasuda Seiki Seisakusho, Nishinomiya City, Hyogo Prefecture, Japan), the decorative laminate was placed so that the recess of the receiving base was covered and the metal layer was on the upper surface as shown in FIG. 4, and a hemispherical shot die with a diameter of 1 / 2 inch was placed in contact with the upper surface of the metal layer, and a 1 kg weight was dropped from a height of 50 cm onto the shot die to deform the laminate into a convex shape (FIG. 5(a)). Next, a cross-shaped cut was made in the polyurethane layer of the laminate deformed into a convex shape with a cutter blade as shown in FIG. 5(b), and the laminate with the cut was subjected to the following heat cycle to check the opening width and peeling width of the polyurethane layer at the cut. Here, the "height" in "50 cm height" refers to the distance from the bottom end of the weight to the top surface of the shot die, as shown on the left side of FIG. 4(a) or FIG. 4(b). The following heat cycle is typically performed continuously: (Thermal Cycle) (1) Heat the container from 23°C to 80°C over one hour. (2) Maintain at 80°C for 18 hours. (3) The temperature is lowered to -30°C over one hour. (4) Keep at -30°C for 4 hours. (5) Heat to 80°C over 1 hour. (6) Keep at 80°C for 18 hours. Repeat steps (3) to (6) above nine times. (7) The temperature is reduced to -30°C over one hour. (8) Keep at -30°C for 4 hours. (9) The temperature is raised from -30°C to 23°C over one hour.
[0063] The decorative laminate of the present disclosure, unlike conventional products, does not have an adhesive layer such as a heat-sensitive polyurethane adhesive layer, which is a flexible layer applied between a polyurethane layer and a metal layer, and therefore the hardness of the entire decorative laminate can be improved. In some embodiments, the decorative laminate of the present disclosure can achieve a pencil hardness of B or more, HB or more, or F or more in the pencil hardness test described below. There is no particular limit to the upper limit of the pencil hardness, but it can be, for example, 3H or less, 2H or less, or H or less.
[0064] The decorative laminate of the present disclosure has excellent corrosion resistance and impact resistance because it contains a polyurethane layer. Therefore, the decorative laminate of the present disclosure can achieve a pass level in the weather resistance test and chemical resistance test described later. In particular, a decorative laminate produced using a two-component curing polyurethane resin composition containing at least one polyol selected from the group consisting of polycaprolactone polyol and polycarbonate polyol, and at least one isocyanate selected from the group consisting of isocyanates having a cyclohexane structure, isocyanates having no carbon-carbon double bonds, and isocyanates having a branched structure can further improve impact resistance. In some embodiments, the decorative laminate of the present disclosure can exhibit impact resistance in which no cracks or peeling occurs in the polyurethane layer that has been deformed into a convex shape when a No. 517 DuPont drop impact tester (manufactured by Yasuda Seiki Seisakusho, Nishinomiya City, Hyogo Prefecture, Japan) is used to cover the recess of a receiving base having a recess, the decorative laminate is positioned so that the metal layer is on the upper surface, and a shooting die having a hemispherical tip with a diameter of 1 / 2 inch is placed in contact with the upper surface of the metal layer, and a 1 kg weight is dropped from a height of 50 cm onto the shooting die.
[0065] In some embodiments, the decorative laminate of the present disclosure includes, in addition to the above-mentioned layers, any additional layer as long as it does not adversely affect the effects of the present invention. Examples of such additional layers include at least one selected from the group consisting of a colored layer, a decorative layer (e.g., a pattern layer, a relief layer), a glittering layer, an adhesive layer, and a release liner. The additional layer can be applied to the entire surface or a part of the laminate. For example, when the colored layer, the decorative layer, and the glittering layer are applied between the polyurethane layer and the primer layer, these layers can be applied to a part of the polyurethane layer and / or the primer layer as long as they do not inhibit the adhesion between the polyurethane layer and the primer layer. Here, when the colored layer and the decorative layer are formed using a two-component curing polyurethane resin composition like the polyurethane layer described above, these layers can be considered as a part of the polyurethane layer of the above-mentioned laminated structure, and in that case, they can be applied to the entire surface of the polyurethane layer and / or the primer layer, and these layers can be formed according to the manufacturing method of the decorative laminate of the present disclosure described above. The adhesive layer as an additional layer is intended to be a layer for attaching the decorative laminate of the present disclosure to a support member, etc., and can be applied to the entire surface or a part of the surface of the metal layer opposite to the surface to which the polyurethane layer is applied. The additional layer may have a three-dimensional shape, such as an embossed pattern, on its surface.
[0066] The decorative laminate of the present disclosure may be, for example, a sheet product, a rolled product wound into a roll, or a three-dimensional object. Here, examples of the three-dimensional object include a laminate processed into a curved shape, a laminate pressed into a predetermined shape, etc. The decorative laminate of the present disclosure has excellent performance such as adhesion between the metal layer and the polyurethane layer, and is unlikely to cause problems such as peeling and tearing even when subjected to three-dimensional molding, so it can be suitably used for three-dimensional molding.
[0067] An article including the decorative laminate of the present disclosure having a three-dimensional shape formed by processing the decorative laminate of the present disclosure can be referred to as a decorative article in the present disclosure. Such a decorative article can be manufactured by subjecting the decorative laminate of the present disclosure to a known molding method, for example, press processing or roll forming. Examples of press processing include press forming, folding, and deep drawing. Such processing methods can be used alone or in combination of two or more.
[0068] As the press forming process, for example, a method can be adopted in which the metal layer side of the decorative laminate of the present disclosure is placed in a female mold of a press die, and then a male mold is pressed into the polyurethane layer side of the decorative laminate to plastically deform the metal layer. In addition, a method can be adopted in which the polyurethane layer side of the decorative laminate of the present disclosure is placed in a female mold of a press die, and then a male mold is pressed into the metal layer side of the decorative laminate to plastically deform the metal layer.
[0069] Roll forming can be performed using a roll forming machine, also known as a tube mill, for example, which uses multiple rolls to sequentially process the decorative laminate of the present disclosure into a curved shape, such as a tube.
[0070] The bending process can be performed, for example, by fixing a portion of the decorative laminate of the present disclosure and bending the unfixed portion at any angle starting from the boundary between the fixed portion and the unfixed portion by applying a mold or manually striking the unfixed portion.
[0071] A resin material or rubber material may be injected into the three-dimensional decorative laminate after processing using an extrusion method or the like, and the laminate may be integrated with such a material.
[0072] In some embodiments, a decorative article having a three-dimensional shape may be provided by applying a support member to a decorative laminate of the present disclosure having a three-dimensional shape, the decorative article comprising the support member and the decorative laminate adhered to the support member.
[0073] The material for the support member is not particularly limited, and examples thereof include resin materials (e.g., polyolefin resin, polyester resin, (meth)acrylic resin, polycarbonate resin, acrylonitrile-butadiene-styrene copolymer), inorganic materials (e.g., glass, ceramic, concrete, gypsum, calcium silicate, natural stone, asphalt), rubber materials, fabric materials (e.g., woven fabric, knitted fabric, nonwoven fabric), metal or metal alloy materials (e.g., iron, aluminum, stainless steel), and wood materials including paper.
[0074] The shape or configuration of the support member is not particularly limited, and may be, for example, a film shape, a plate shape, or a three-dimensional shape, and may be a single-layer structure, a laminated structure, or a composite structure in which multiple members of different shapes or materials are combined.
[0075] The decorative article containing the decorative laminate of the present disclosure can be used in various applications. Examples of such applications include signs; signs; various interior or exterior parts, such as interior or exterior parts of vehicles such as automobiles, railways, aircraft, and ships (for example, roof members, pillar members, door trim members, instrument panel members, front members such as bonnets, bumper members, fender members, side sill members, and interior panel members), and interior or exterior parts of buildings (for example, roof members such as window glass, doors, sashes, and tiles, exterior wall members, wallpaper, etc.); electrical appliances such as personal computers, smartphones, mobile phones, refrigerators, and air conditioners; stationery; furniture; desks; various containers such as cans, etc. Among them, the decorative laminate of the present disclosure has excellent decorative performance such as metallic luster, so that the decorative article containing the decorative laminate of the present disclosure can be suitably used as an interior or exterior part of a vehicle or building.
[0076] There is no particular limitation on the method of applying the decorative laminate of the present disclosure to the supporting member (adherend) constituting the decorative article, and any known method can be used as appropriate. For example, there can be mentioned injection molding methods such as hand application, insert injection molding, in-mold molding, two-color injection molding, core-back injection molding, and sandwich injection molding. EXAMPLES
[0077] The following examples illustrate specific embodiments of the present disclosure, but are not intended to limit the present invention. All parts and percentages are by weight unless otherwise specified. Numerical values inherently contain errors resulting from measurement principles and measuring devices. Numerical values are presented with significant digits with normal rounding.
[0078] The products used in this example are shown in Table 1 below.
[0079] [Table 1]
[0080] Test Example 1 In Test Example 1, the impact resistance, moldability, and weather resistance of the test sample were evaluated.
[0081] Preparation of two-component curable polyurethane resin composition BM for colored layer (metallic blue color) A blue metallic paint was prepared by uniformly mixing 3 parts by weight of pearlescent pigment, 0.5 parts by weight of black pigment, 0.2 parts by weight of purple pigment, 30 parts by weight of Desmophen (trademark) A565 (acrylic polyol), 30.1 parts by weight of toluene, 13.9 parts by weight of ethyl acetate, 6.9 parts by weight of butyl acetate, 6 parts by weight of xylene, 5.3 parts by weight of ethylbenzene, and 4.1 parts by weight of isobutyl acetate. A two-component curing polyurethane resin composition BM for a colored layer was prepared by uniformly mixing 100 parts by weight of the obtained blue metallic paint and 7 parts by weight of VESTNAT (trademark) T1890E.
[0082] Preparation of two-component curable polyurethane resin composition GM for colored layer (gold metallic color) 5 parts by mass of aluminum lustrous agent, 0.5 parts by mass of yellow pigment, 0.1 parts by mass of black pigment, 0.1 parts by mass of white pigment, 30 parts by mass of Desmophen (trademark) A565 (acrylic polyol), 29.2 parts by mass of toluene, 13.4 parts by mass of ethyl acetate, 6.9 parts by mass of butyl acetate, 5.9 parts by mass of xylene, 4.9 parts by mass of ethylbenzene, and 4 parts by mass of isobutyl acetate were uniformly mixed to prepare a gold metallic paint. 100 parts by mass of the obtained gold metallic paint and 7 parts by mass of VESTNAT (trademark) T1890E were uniformly mixed to prepare a two-component curing polyurethane resin composition GM for the colored layer.
[0083] Preparation of two-component curable polyurethane resin composition C for surface layer (colorless) A two-component curing polyurethane resin composition C for the surface layer was prepared by uniformly mixing 100 parts by weight of PLAXEL (trademark) 205H, 2.0 parts by weight of TINUVIN (trademark) 292, 2.0 parts by weight of TINUVIN (trademark) 99-2, 25.0 parts by weight of butyl acetate, 0.15 parts by weight of catalyst, and 150 parts by weight of VESTNAT (trademark) T1890E. The solid content of the composition C was 74.9%.
[0084] Preparation of two-component curable polyurethane resin composition BB for surface layer (blue-black color) 35 parts by weight of copper iron manganese pigment, 17.5 parts by weight of Desmophen A565 (acrylic polyol), 21.4 parts by weight of xylene, 15.2 parts by weight of ethylbenzene, 6.8 parts by weight of butyl acetate, and 4.1 parts by weight of isobutyl acetate were uniformly mixed to prepare a blue-black mill base paint. Next, 100 parts by weight of Plaxel 205H, 2.0 parts by weight of TINUVIN 292, 2.0 parts by weight of TINUVIN 99-2, 25.0 parts by weight of butyl acetate, 0.15 parts by weight of catalyst, 150 parts by weight of VESTNAT T1890E, and 8.0 parts by weight of blue-black mill base paint were uniformly mixed to prepare a two-component curing polyurethane resin composition BB for the surface layer. Here, the solid content of the composition BB was 74.3%.
[0085] Preparation of two-component curable polyurethane resin composition RB for surface layer (red / black color) 11.6 parts by mass of carbon black pigment, 11.6 parts by mass of Desmophen (trademark) A565 (acrylic polyol), 30.9 parts by mass of xylene, 26.2 parts by mass of ethylbenzene, 13.8 parts by mass of butyl acetate, and 5.9 parts by mass of isobutyl acetate were uniformly mixed to prepare a red-black mill base paint. Next, 100 parts by mass of Plaxel (trademark) 205H, 2.0 parts by mass of TINUVIN (trademark) 292, 2.0 parts by mass of TINUVIN (trademark) 99-2, 25.0 parts by mass of butyl acetate, 0.15 parts by mass of catalyst, 150 parts by mass of VESTNAT (trademark) T1890E, and 0.8 parts by mass of the red-black mill base paint were uniformly mixed to prepare a two-component curing polyurethane resin composition RB for the surface layer. Here, the solid content of the composition RB was 74.8%.
[0086] Example 1 After applying the two-component curing polyurethane resin composition C for the surface layer to PK-002 with a bar coater, it was placed in a hot air oven at 80°C for 4 minutes and dried in an uncured state to prepare a colorless polyurethane precursor coating film with a thickness of about 0.05 mm. Lumirror (trademark) T60 was laminated onto the coating film to prepare a three-layer film, which was then left at room temperature for 24 hours.
[0087] Silane coupling agent Z-6011 was diluted to 3% with alcohol, and then applied by wiping to a stainless steel plate (SUS430#8) as a metal substrate, and baked at 200°C for 5 minutes to form a primer layer of about 1 micrometer thickness. While the residual heat from baking was still remaining, PK-002 was peeled off from the three-layer film, and the uncured polyurethane precursor coating surface was applied to the primer layer, and left at room temperature for 24 hours. After heating at 80°C for 1 hour, Lumirror (trademark) T60 was peeled off to obtain a test sample of the decorative laminate.
[0088] (Examples 2 to 6) Test samples of the decorative laminates of Examples 2 to 6 were obtained in the same manner as in Example 1, except that the types of PET films applied to the metal substrate, the surface layer, and the coating film of the surface layer were changed to those shown in Table 2.
[0089] Example 7 A two-component curable polyurethane resin composition BM for colored layer was applied onto a biaxially stretched PET film (G2) using a bar coater, and then placed in a hot air oven at 80°C for 20 minutes to form a polyurethane precursor colored coating film with a thickness of about 20 micrometers, which was dried in an uncured state. Next, a two-component curable polyurethane resin composition C for surface layer was applied onto the colored coating film using a bar coater, and then placed in a hot air oven at 80°C for 4 minutes to prepare a colorless polyurethane precursor coating film with a thickness of about 0.05 mm, which was dried in an uncured state. Lumirror (trademark) T60 was laminated onto the coating film to prepare a four-layer film, which was then left at room temperature for 24 hours.
[0090] The acrylic primer KBS17A / B was diluted with MEK, and applied by wiping to a stainless steel plate (SUS430BA) as a metal substrate, and baked at 200°C for 5 minutes to form a primer layer approximately 1 micrometer thick. While the residual heat from the baking process was still present, G2 was peeled off from the four-layer film, and the uncured polyurethane precursor colored coating surface was applied to the primer layer, and the film was left at room temperature for 24 hours. After heating at 80°C for 1 hour, Lumirror (trademark) T60 was peeled off to obtain a test sample of the decorative laminate.
[0091] Example 8 Acrylic primer KBS17A / B was diluted with MEK, and the diluted solution was applied by wiping to a stainless steel plate (SUS430BA) as a metal substrate, and baked at 200°C for 5 minutes to form a primer layer with a thickness of about 1 micrometer. A two-component curing polyurethane resin composition GM for colored layer was applied on the primer layer with a bar coater, and then the mixture was placed in a hot air oven at 80°C for 20 minutes to form a polyurethane precursor colored coating film with a thickness of about 20 micrometers, which was dried in an uncured state. Next, a two-component curing polyurethane resin composition C for surface layer was applied to the colored coating film with a bar coater, and then the mixture was placed in a hot air oven at 80°C for 4 minutes to prepare a colorless polyurethane precursor coating film with a thickness of about 0.05 mm, which was dried in an uncured state. Lumirror (trademark) T60 was laminated on the coating film and left at room temperature for 24 hours. After heating at 80°C for 1 hour, Lumirror (trademark) T60 was peeled off to obtain a test sample of a decorative laminate.
[0092] (Comparative Examples 1 and 2) Coated plates 1 and 2 were used as test samples for Comparative Examples 1 and 2. Note that the surface layers of Coated Plates 1 and 2 were not polyurethane layers, and therefore in Table 2, the resin components constituting these surface layers are shown in parentheses.
[0093] <Physical property evaluation test 1> The properties of each test sample were evaluated by carrying out the following tests, the results of which are shown in Table 2.
[0094] (Appearance test: decorativeness) The appearance such as gloss of the test sample was visually confirmed before molding and after the three-dimensional moldability test described later (i.e., after molding) to evaluate the decorativeness.
[0095] (Impact resistance test: Impact resistance) Using a No. 517 DuPont drop impact tester (manufactured by Yasuda Seiki Seisakusho, Nishinomiya City, Hyogo Prefecture, Japan), the recess of the receiving platform was covered, and the test sample was placed so that the metal substrate of the test sample was facing up. A shooting die with a hemispherical tip with a diameter of 1 / 2 inch was placed in contact with the top surface of the metal substrate. A 1 kg weight was then dropped from a height of 50 cm onto the shooting die. The polyurethane layer (surface layer, colored layer) that had been deformed into a convex shape was then visually inspected for cracks, peeling, and other abnormalities.
[0096] (Three-dimensional moldability test: moldability (mold shape)) The test sample was punched out into the specified shape using a press and a punching die so that the dimensions would be as shown in Figure 3(c) after molding, and then the sample was molded into the molding shape shown in Figure 3(c) using a press and a press die. The polyurethane layer (surface layer, colored layer) was visually inspected for any abnormalities such as cracks or peeling.
[0097] (Weather resistance test: Weather resistance) The test samples of the molding shape obtained in the above three-dimensional formability test were placed on an exposure table facing south at an angle of 45 degrees, which was set up on land approximately 1 km away from the coast of Numazu City, Shizuoka Prefecture, Japan, for two years, and then visually inspected for any noticeable color or gloss changes, cracks, peeling of the polyurethane layer (surface layer, colored layer), or any abnormalities such as rust on the metal substrate.
[0098] [Table 2]
[0099] Test Example 2 In Test Example 2, the impact resistance, opening resistance, adhesion, and hardness of the test samples were evaluated depending on whether or not they had a primer layer and whether or not they had an adhesive layer between the primer layer and the polyurethane layer.
[0100] Preparation of Polyester Adhesive Composition for Adhesive Layer A polyester adhesive composition for the adhesive layer was prepared by uniformly mixing 30 parts by weight of Elitel (trademark) UE3230, 70 parts by weight of MEK, and 2 parts by weight of Coronate (trademark) HL.
[0101] Preparation of Polyurethane Adhesive Composition for Adhesive Layer A polyurethane adhesive composition for the adhesive layer was prepared by uniformly mixing 20 parts by weight of Desmocol (trademark) 530, 80 parts by weight of MEK, and 0.2 parts by weight of Desmodur (trademark) RFE.
[0102] Preparation of two-component curable polyurethane resin composition B for surface layer (black color (concealing property)) 7.7 parts by weight of carbon black pigment, 1.9 parts by weight of titanium oxide pigment, 28.3 parts by weight of Desmophen (trademark) A565 (acrylic polyol), 25.9 parts by weight of xylene, 21.2 parts by weight of ethylbenzene, 9.8 parts by weight of butyl acetate, and 5.2 parts by weight of isobutyl acetate were uniformly mixed to prepare a black mill base paint. Next, 100 parts by weight of Plaxel (trademark) 205H, 2.0 parts by weight of TINUVIN (trademark) 292, 2.0 parts by weight of TINUVIN (trademark) 99-2, 25.0 parts by weight of butyl acetate, 0.15 parts by weight of catalyst, 150 parts by weight of VESTNAT (trademark) T1890E, and 40.0 parts by weight of black mill base paint were uniformly mixed to prepare a two-component curing polyurethane resin composition B for the surface layer. Here, the solid content of the composition B was 74.1%.
[0103] Example 9 A test sample of the decorative laminate of Example 9 was obtained in the same manner as in Example 1.
[0104] (Examples 10 to 11) Except for changing the metal substrate to one shown in Table 3, the same procedure as in Example 1 was carried out to obtain test samples of the decorative laminates of Examples 10 and 11.
[0105] Comparative Example 3 A two-component curing polyurethane resin composition C for surface layer was applied to PK-002 with a bar coater, and then the mixture was placed in a hot air oven at 80°C for 4 minutes to prepare a colorless polyurethane precursor coating film with a thickness of about 0.05 mm, which was dried in an uncured state. Lumirror (trademark) T60 was laminated onto the coating film to prepare a three-layer film, which was then left at room temperature for 24 hours. Next, a polyester adhesive composition for adhesive layer was applied to PK-002 with a bar coater, and the mixture was placed in a hot air oven at 80°C for 4 minutes to prepare a two-layer film including an adhesive layer with a thickness of about 20 micrometers. After peeling PK-002 from the three-layer film including the polyurethane precursor coating film, the two-layer film was applied so that the adhesive layer was in contact with the polyurethane precursor coating film, and a four-layer film including PK-002 / adhesive layer / polyurethane precursor coating film / T60 (PET film) was prepared.
[0106] Silane coupling agent Z-6011 was diluted to 3% with alcohol, and then applied by wiping to a stainless steel plate (SUS430#8) as a metal substrate, and baked at 200°C for 5 minutes to form a primer layer approximately 1 micrometer thick. While the residual heat from baking was still present, PK-002 was peeled off from the four-layer film, an adhesive layer was applied to the primer layer, and the film was left at room temperature for 24 hours. After heating at 80°C for 1 hour, Lumirror™ T60 was peeled off to obtain a test sample of the decorative laminate.
[0107] (Comparative Examples 4 to 5) Except for changing the metal substrate to one shown in Table 3, test samples of the decorative laminates of Comparative Examples 4 to 5 were obtained in the same manner as in Comparative Example 3.
[0108] Example 12 Silane coupling agent Z-6011 was diluted to 3% with alcohol, and the diluted solution was applied by wiping to a stainless steel plate (SUS430BA) as a metal substrate, and baked at 200°C for 5 minutes to form a primer layer with a thickness of about 1 micrometer. Two-component curing polyurethane resin composition C for surface layer was applied to the primer layer with a bar coater, and then placed in a hot air oven at 80°C for 4 minutes to prepare a colorless polyurethane precursor coating film with a thickness of about 0.05 mm that was dried in an uncured state. Lumirror (trademark) T60 was laminated on the coating film and left at room temperature for 24 hours. After heating at 80°C for 1 hour, Lumirror (trademark) T60 was peeled off to obtain a test sample of the decorative laminate.
[0109] (Example 13) A test sample of the decorative laminate of Example 13 was obtained in the same manner as in Example 7.
[0110] Comparative Example 6 A two-component curable polyurethane resin composition BM for colored layer was applied onto a biaxially stretched PET film (G2) using a bar coater, and then placed in a hot air oven at 80°C for 20 minutes to form a polyurethane precursor colored coating film with a thickness of about 20 micrometers, which was dried in an uncured state. Next, a two-component curable polyurethane resin composition C for surface layer was applied onto the colored coating film using a bar coater, and then placed in a hot air oven at 80°C for 4 minutes to prepare a colorless polyurethane precursor coating film with a thickness of about 0.05 mm, which was dried in an uncured state. Lumirror (trademark) T60 was laminated onto the coating film to prepare a four-layer film, which was then left at room temperature for 24 hours.
[0111] A polyurethane adhesive composition for adhesive layer was applied to PK-002 with a bar coater, and then placed in a hot air oven at 80°C for 4 minutes to produce a two-layer film including an adhesive layer of about 20 micrometers. After peeling off the biaxially stretched PET film (G2) from the four-layer film including the colored layer, the two-layer film was applied so that the adhesive layer was in contact with the colored layer, producing a five-layer film including PK-002 / adhesive layer / polyurethane precursor colored coating film / polyurethane precursor surface coating film / T60 (PET film), which was then left at room temperature for 24 hours.
[0112] The acrylic primer KBS17A / B was diluted with MEK, and applied by wiping to a stainless steel plate (SUS430BA) as a metal substrate, and baked at 200°C for 5 minutes to form a primer layer approximately 1 micrometer thick. While the residual heat from baking was still present, PK-002 was peeled off from the 5-layer film, an adhesive layer was applied to the primer layer, and the film was left at room temperature for 24 hours. After heating at 80°C for 1 hour, Lumirror™ T60 was peeled off to obtain a test sample of the decorative laminate.
[0113] Comparative Example 7 A test sample of the decorative laminate of Comparative Example 7 was obtained in the same manner as in Comparative Example 6, except that a polyester adhesive composition for the adhesive layer was used instead of the polyurethane adhesive composition for the adhesive layer.
[0114] Example 14 Acrylic primer KBS17A / B was diluted with MEK, and the diluted solution was applied by wiping to a stainless steel plate (SUS430BA) as a metal substrate, and baked at 200°C for 5 minutes to form a primer layer with a thickness of about 1 micrometer. The two-component curing polyurethane resin composition B for the surface layer was applied onto the primer layer with a bar coater, and then placed in a hot air oven at 80°C for 4 minutes to prepare a black, opaque polyurethane precursor coating film with a thickness of about 0.05 mm that was dried in an uncured state. Lumirror (trademark) T60 was laminated onto the coating film and left at room temperature for 24 hours. After heating at 80°C for 1 hour, Lumirror (trademark) T60 was peeled off to obtain a test sample of the decorative laminate.
[0115] Comparative Example 8 Two-component curable polyurethane resin composition C for surface layer was applied to PK-002 with a bar coater, and then placed in a hot air oven at 80°C for 4 minutes to prepare a colorless polyurethane precursor coating film approximately 50 micrometers thick that was dried in an uncured state. Lumirror (trademark) T60 was laminated onto the coating film to prepare a three-layer film, which was then left at room temperature for 24 hours.
[0116] A stainless steel plate (SUS304#8) as a metal substrate without a primer layer was heated to 200°C, and while still hot, PK-002 was peeled off from the three-layer film, and the uncured polyurethane precursor coating surface was applied to the primer layer and left at room temperature for 24 hours. After heating at 80°C for 1 hour, Lumirror (trademark) T60 was peeled off to obtain a test sample of the decorative laminate.
[0117] Comparative Example 9 After applying the two-component curing polyurethane resin composition C for the surface layer to PK-002 with a bar coater, it was placed in a hot air oven at 80°C for 4 minutes and dried in an uncured state to prepare a colorless polyurethane precursor coating film with a thickness of about 0.05 mm. Lumirror (trademark) T60 was laminated onto the coating film to prepare a three-layer film, which was then left at room temperature for 24 hours.
[0118] 3M™ Adhesion Promoter 86A was diluted 3 times with isopropyl alcohol and applied to a stainless steel plate (SUS304#8) as a metal substrate by wiping, then placed in a 200°C hot air oven for 3 minutes to form an adhesive layer of about 1 micrometer thickness. While still hot, PK-002 was peeled off from the three-layer film, and the uncured polyurethane precursor coating surface was applied to the adhesive layer and left at room temperature for 24 hours. After heating at 80°C for 1 hour, Lumirror™ T60 was peeled off to obtain a test sample of the decorative laminate.
[0119] <Physical property evaluation test 2> The properties of each test sample were evaluated by carrying out the appearance test and impact resistance test of the above-mentioned Physical Property Evaluation Test 1, as well as the following tests. The results are shown in Table 3.
[0120] (Heat resistance test: opening resistance) Using a No. 517 DuPont drop impact tester (manufactured by Yasuda Seiki Seisakusho, Nishinomiya City, Hyogo Prefecture, Japan), a test sample was placed so that the recess of a receiving table having a recess was covered and the metal substrate was on the upper surface, and a shooting die having a hemispherical shape with a diameter of 1 / 2 inch at the tip was brought into contact with the upper surface of the metal substrate, and a weight of 1 kg was dropped from a height of 50 cm onto the shooting die to deform the test sample into a convex shape. A cross-shaped cut was made in the polyurethane layer of the test sample deformed into a convex shape with a cutter blade, and the following heat cycle was applied to the test sample with the cut. The opening width and peeling width of the polyurethane layer at the cut were confirmed using a vernier caliper. Here, in this embodiment, the case where the opening width and peeling width were both 0.5 mm or less was evaluated as "pass", and the case where either the opening width or the peeling width was more than 0.5 mm was evaluated as "fail": (Thermal Cycle) (1) Heat the container from 23°C to 80°C over one hour. (2) Maintain at 80°C for 18 hours. (3) The temperature is lowered to -30°C over one hour. (4) Keep at -30°C for 4 hours. (5) Heat to 80°C over 1 hour. (6) Keep at 80°C for 18 hours. Repeat steps (3) to (6) above nine times. (7) The temperature is reduced to -30°C over one hour. (8) Keep at -30°C for 4 hours. (9) The temperature is raised from -30°C to 23°C over one hour.
[0121] (Water resistance test: Adhesion) The test sample was immersed in 40°C water for 240 hours, taken out, wiped off the water, and left for 1 hour. Then, a total of 100 1mm squares (10x10) were cut with a cutter on the polyurethane layer of the test sample. Cellophane tape (registered trademark) was applied to the 100 squares and the cellophane tape (registered trademark) was immediately peeled off vigorously to check the number of remaining squares where the polyurethane layer was not peeled off. Here, the number of remaining squares of 90 / 100 or more can be considered as "passed", and 89 / 100 or less can be considered as "failed".
[0122] (Pencil hardness test: hardness) A pencil lead, which had been cut into a cylindrical shape and had its tip smoothed with sandpaper, was placed at a 45 degree angle against the polyurethane layer surface of the test sample, and the pencil lead was moved 10 mm at a speed of 600 mm / min while applying a load of 750 g, rubbing the surface of the polyurethane layer with the pencil lead. Different locations were tested five times each using pencils of hardness from 6B to HB, and the hardness of the test sample was determined from the hardness of the pencil used when the surface of the polyurethane layer was not scratched four or more times. Here, HB can be considered as a "pass" and B or lower as a "fail".
[0123] [Table 3]
[0124] Test Example 3 In Test Example 3, the chemical resistance, moldability, and weather resistance of the test sample were evaluated.
[0125] Example 15 A test sample of the decorative laminate of Example 15 was obtained in the same manner as in Example 1.
[0126] (Example 16) After applying the two-component curing polyurethane resin composition C for the surface layer to PK-002 with a bar coater, it was placed in a hot air oven at 80°C for 4 minutes and dried in an uncured state to prepare a colorless polyurethane precursor coating film with a thickness of about 0.05 mm. Lumirror (trademark) T60 was laminated onto the coating film to prepare a three-layer film, which was then left at room temperature for 24 hours.
[0127] A stainless steel plate (SUS430#8) was plasma-treated in a nitrogen gas atmosphere as a metal substrate, and then a silane coupling agent Z-6011 diluted to 3% with alcohol was wiped onto the plasma-treated surface of the metal substrate and baked at 200°C for 5 minutes to form a primer layer approximately 1 micrometer thick. While the residual heat from the baking process was still present, PK-002 was peeled off from the three-layer film, and the uncured polyurethane precursor coating surface was applied to the primer layer and left at room temperature for 24 hours. After heating at 80°C for 1 hour, Lumirror™ T60 was peeled off to obtain a test sample of the decorative laminate.
[0128] (Example 17) A test sample of the decorative laminate of Example 17 was obtained in the same manner as in Example 14.
[0129] Comparative Example 10 As a test sample of Comparative Example 10, a single stainless steel plate (SUS430#8) was used.
[0130] <Physical property evaluation test 3> The properties of each test sample were evaluated by carrying out the following tests, the results of which are shown in Table 4.
[0131] (Appearance test: decorativeness) The appearance such as gloss of the test sample was visually confirmed before molding and after the three-dimensional moldability test described later (i.e., after molding) to evaluate the decorativeness.
[0132] (Chemical resistance test: Chemical resistance) In the test samples of Examples 15 to 17, 1% by mass of hydrochloric acid was dropped onto the surface of the polyurethane layer, and in the test sample of Comparative Example 9, 1% by mass of hydrochloric acid was dropped onto the surface of the metal substrate. The samples were then placed in a hot air oven at 40°C for 1 hour, after which the surfaces onto which the hydrochloric acid had been dropped were washed with water and visually inspected for any traces such as discoloration.
[0133] (Three-dimensional moldability test: moldability (hat shape)) The test sample was cut into a circle with a diameter of approximately 135 mm, and formed into a hat shape with a height of 45 mm and a diameter of 64 mm as shown in Figure 5 using a press and a press die. The polyurethane layer or metal substrate was then visually inspected for any abnormalities such as cracks.
[0134] (Weather resistance test: Weather resistance) The hat-shaped test samples obtained in the above three-dimensional formability test were placed on an exposure table facing south at an angle of 45 degrees, which was set up on land approximately 1 km away from the coast of Numazu City, Shizuoka Prefecture, Japan, for two years, and then visually inspected for any abnormalities such as significant color or gloss changes, cracks, peeling of the polyurethane layer, or rust on the metal substrate.
[0135] [Table 4]
[0136] It will be apparent to those skilled in the art that the above-described embodiments and examples can be modified in various ways without departing from the basic principles of the present invention, and that various improvements and modifications of the present invention can be made without departing from the spirit and scope of the present invention. [Explanation of symbols]
[0137] 100, 200 Decorative laminate 101, 201 metal layer 103, 203 Primer layer 105 Adhesive layer 107, 207 Polyurethane layer 400 weight 401 Shooting Type 403 Test sample (decorative laminate) 405 Cradle
[0138] Some embodiments of the present disclosure are described in [Item 1] to [Item 10] below. [Item 1] A method for producing a decorative laminate for three-dimensional forming, comprising: Providing a metal layer; applying a primer layer containing at least one selected from the group consisting of an organosilicon compound and a (meth)acrylic resin to the metal layer; applying a layer of a two-component curable polyurethane precursor comprising a polyol and an isocyanate directly to the primer layer; and reacting the two-component curing polyurethane precursor layer to form a polyurethane layer. A method for producing a decorative laminate for three-dimensional forming. [Item 2] 2. The method according to item 1, wherein the polyurethane precursor layer is an uncured polyurethane sheet or an uncured polyurethane coating layer. [Item 3] 3. The method according to item 1 or 2, wherein the polyol is at least one selected from the group consisting of polycaprolactone polyols and polycarbonate diols, and the isocyanate is at least one selected from the group consisting of isocyanates having a cyclohexane structure, isocyanates having no carbon-carbon double bonds, and isocyanates having a branched structure. [Item 4] 4. The method according to any one of items 1 to 3, wherein the primer layer has a thickness of about 5 micrometers or less. [Item 5] A decorative laminate for three-dimensional fabrication, comprising, in order, a metal layer, a primer layer and a polyurethane layer, the primer layer contains at least one selected from the group consisting of an organosilicon compound and a (meth)acrylic resin, the polyurethane layer comprises a cured reaction product of a two-component curing polyurethane resin composition containing a polyol and an isocyanate, the polyurethane layer is applied directly to the primer layer; and When the polyurethane layer of the laminate is subjected to the following water resistance test, the polyurethane layer achieves a remaining square count of 90 / 100 or more, and When the polyurethane layer of the laminate is subjected to the following heat resistance test, the polyurethane layer exhibits a maximum opening width or peel width of 0.5 mm or less. Decorative laminates for 3D processing: <Water resistance test> The laminate is immersed in water at 40°C for 240 hours, the laminate is taken out, the moisture is wiped off, and the laminate is left to stand for 1 hour. After that, a total of 100 1 mm squares (10 x 10) are formed in the polyurethane layer of the laminate with a cutter, and Scotch tape (registered trademark) is applied to the 100 squares. The Scotch tape (registered trademark) is then immediately removed to count the number of squares remaining where the polyurethane layer has not peeled off. <Heat resistance test> Using a DuPont drop impact tester No. 517, the laminate is placed so that the recess of a receiving base is covered and the metal layer is on the upper surface, and a hemispherical die with a diameter of 1 / 2 inch at the tip is brought into contact with the upper surface of the metal layer. A weight of 1 kg is dropped from a height of 50 cm onto the die to deform the laminate into a convex shape, and a cross-shaped cut is made in the polyurethane layer of the laminate that has been deformed into the convex shape with a cutter blade. The laminate is subjected to the following heat cycle, and the opening width and peeling width of the polyurethane layer at the cut are confirmed: (Thermal Cycle) (1) Heat the container from 23°C to 80°C over one hour. (2) Maintain at 80°C for 18 hours. (3) The temperature is lowered to -30°C over one hour. (4) Keep at -30°C for 4 hours. (5) Heat to 80°C over 1 hour. (6) Keep at 80°C for 18 hours. The above steps (3) to (6) are repeated nine times. (7) The temperature is reduced to -30°C over one hour. (8) Keep at -30°C for 4 hours. (9) The temperature is raised from -30°C to 23°C over one hour. [Item 6] Item 6. The laminate according to item 5, wherein the polyol is at least one selected from the group consisting of polycaprolactone polyols and polycarbonate polyols, and the isocyanate is at least one selected from the group consisting of isocyanates having a cyclohexane structure, isocyanates having no carbon-carbon double bonds, and isocyanates having a branched structure. [Item 7] 7. The laminate according to item 5 or 6, wherein the primer layer has a thickness of about 5 micrometers or less. [Item 8] 8. The laminate according to any one of items 5 to 7, wherein a DuPont drop impact tester is used to cover a recessed portion of a receiving base having a recess, the laminate is arranged so that the metal layer is on the upper surface, and a shooting die having a hemispherical shape with a tip having a diameter of 1 / 2 inch is brought into contact with the upper surface of the metal layer. In this state, a weight of 1 kg is dropped from a height of 50 cm onto the shooting die, and no cracks or peeling occurs in the polyurethane layer that has been deformed into a convex shape. [Item 9] 9. A decorative article comprising the laminate according to any one of items 5 to 8, having a three-dimensional shape. [Item 10] 9. A method for producing a decorative article, comprising pressing or roll forming the laminate according to any one of items 5 to 8.
Claims
1. A method for producing a decorative laminate for three-dimensional forming, comprising: Providing a metal layer; applying a primer layer to the metal layer, the primer layer comprising at least one selected from the group consisting of an organosilicon compound and a (meth)acrylic resin; applying a layer of a two-component curable polyurethane precursor comprising a polyol and an isocyanate directly to the primer layer; reacting the two-component curing polyurethane precursor layer to form a polyurethane layer. A method for producing a decorative laminate for three-dimensional forming.
2. The method according to claim 1 , wherein the polyurethane precursor layer is an uncured polyurethane sheet or an uncured polyurethane coating layer.
3. The method according to claim 1 or 2, wherein the polyol is at least one selected from the group consisting of polycaprolactone polyols and polycarbonate polyols, and the isocyanate is at least one selected from the group consisting of isocyanates having a cyclohexane structure, isocyanates having no carbon-carbon double bonds, and isocyanates having a branched structure.
4. The method according to claim 1 or 2, wherein the primer layer has a thickness of 5 micrometers or less.
5. A decorative laminate for three-dimensional fabrication, comprising, in order, a metal layer, a primer layer and a polyurethane layer, the primer layer comprises at least one selected from the group consisting of an organosilicon compound and a (meth)acrylic resin, the polyurethane layer comprises a cured reaction product of a two-component curing polyurethane resin composition containing a polyol and an isocyanate, the polyurethane layer is applied directly to the primer layer; and When the polyurethane layer of the laminate is subjected to the following water resistance test, the polyurethane layer achieves a remaining square count of 90 / 100 or more, and When the polyurethane layer of the laminate is subjected to the following heat resistance test, the polyurethane layer exhibits a maximum opening width or peel width of 0.5 mm or less. Decorative laminates for 3D processing: <Water resistance test> The laminate is immersed in water at 40°C for 240 hours, the laminate is taken out, the moisture is wiped off, and the laminate is left to stand for 1 hour. Then, a total of 100 1 mm squares (10 x 10) are formed in the polyurethane layer of the laminate with a cutter, and Scotch tape (registered trademark) is applied to the 100 squares. The Scotch tape (registered trademark) is then immediately removed to count the number of squares remaining where the polyurethane layer has not peeled off. <Heat resistance test> Using a DuPont drop impact tester No. 517, the laminate is placed so that the recess of a receiving base having a recess is covered and the metal layer is on the upper surface, and a hemispherical shot die having a diameter of 1 / 2 inch is brought into contact with the upper surface of the metal layer, and a weight of 1 kg is dropped from a height of 50 cm onto the shot die to deform the laminate into a convex shape, and a cross-shaped cut is made in the polyurethane layer of the laminate deformed into the convex shape with a cutter blade. The laminate is subjected to the following heat cycle, and the opening width and peeling width of the polyurethane layer at the cut are confirmed: (Thermal Cycle) (1) The temperature is increased from 23°C to 80°C over one hour. (2) Maintain at 80°C for 18 hours. (3) The temperature is lowered to -30°C over one hour. (4) Keep at -30°C for 4 hours. (5) The temperature is raised to 80° C. over 1 hour. (6) Maintain at 80°C for 18 hours. The above steps (3) to (6) are repeated nine times. (7) The temperature is lowered to -30°C over one hour. (8) Keep at -30°C for 4 hours. (9) The temperature is raised from -30°C to 23°C over one hour.
6. The laminate according to claim 5, wherein the polyol is at least one selected from the group consisting of polycaprolactone polyols and polycarbonate polyols, and the isocyanate is at least one selected from the group consisting of isocyanates having a cyclohexane structure, isocyanates having no carbon-carbon double bonds, and isocyanates having a branched structure.
7. The laminate according to claim 5 or 6, wherein the primer layer has a thickness of 5 micrometers or less.
8. 7. The laminate according to claim 5 or 6, wherein the laminate is placed so that the metal layer is on the upper surface, and a hemispherical shot die having a diameter of 1 / 2 inch is placed on the upper surface of the metal layer, and a weight of 1 kg is dropped from a height of 50 cm onto the shot die using a DuPont drop impact tester No.
517. The laminate according to claim 5 or 6, wherein the polyurethane layer deformed into a convex shape has no cracks or peeling.
9. A decorative article comprising the laminate according to claim 5 or 6, having a three-dimensional shape.
10. A method for producing a decorative article, comprising pressing or roll forming the laminate according to claim 5 or 6.
Citation Information
Patent Citations
Polyurethane resin excellent in extension properties at high temperature
JP1993155976A
Film for forming ornamental layer, ornamental article and production process for ornamental article
JP2007297569A